A study of α-Adrenoceptor agonists on porcine nasal and extra-nasal vasculature: insight into decongestant activity - Abdulrahman, Aseel (2019)
Background and purposes: Sympathomimetics have long been used as medications to relieve the symptoms associated with nasal congestion, but in the last 15 years, the worldwide market has moved from largely topical formulation to oral consumption. Many of the existing drugs are thought to cause vasoconstriction by activating α-adrenoceptors present on nasal mucosa and reduce local blood flow and swelling. This thesis aims to re-evaluate the activity of various sympathomimetic drugs on the nasal and extra-nasal blood vessels and better characterise the pharmacological characteristics of α-adrenoceptors on these vessels. In addition to that, I have explored the potential for lithium ions to modify the action of directly-acting sympathomimetics on both nasal and extra-nasal blood vessels and vasculature.